A qualitative investigation into shariah governance attributes, supervision procedures and auditing in Saudi Islamic banks - Alahmadi, Hatem Abdulaziz (2020)
The primary aim of Islamic banks (IBs) is to fulfill stakeholders’ needs for operational conformity to religious precepts. However, Saudi Arabia does not either issue any regulations related to Islamic banking nor special license for IBs, thereby, treating them on equal terms with the conventional banks. This is so in spite of the fact that Saudi Arabia is the largest player in the global Islamic finance sector, with total assets worth US$ 343b in 2015 and expected to rise to US$ 766b by 2020. At the same time most of previous research focused on customer aspects and disclosure and these studies are narrow in their approach and employed quantitative methods. Thus, this study seeks to investigate the extent to which Saudi Islamic banks and Islamic windows are complying with Shariah by exploring their current procedures of Shariah governance (SG). It employed agency theory, institutional theory and stakeholder theory in explaining governance mechanizes and factors affecting the Shariah compliance. In an attempt to attain the main objective of the research, this study explored the current Shariah governance system used by Saudi banks and the factors affecting the system. In addition, it also identified the current roles, attributes and procedures followed by SB members, identified the current attributes and functions of Shariah auditors, and investigated the procedures related to Shariah non-compliant income. Furthermore, the study followed a qualitative research approach by using semi-structured interviews with fifty selected participants related to SG in all Saudi IBs, four full-fledged Islamic banks (FFIBs) and eight Islamic windows (IWs) of conventional banks. The participants were categorized into two: internal and external participants. The internal participants include Shariah board (SB) members, Shariah department staff, internal auditors and managers whereas the external include individuals working with organizations other than the banks e.g. staff of Saudi Arabian Monetary Authority (SAMA), Islamic Economic Institute (IEI), Higher Institute of the Judiciary and Islamic Research and Training Institute (IRTI), General Authority of Zakat & Tax (GAZT) and Saudi Organization of Certified Public Accountants (SOCPA). In addition to supplemented analysis of relevant archival evidence such as audit checklist for some products. Result of the study indicated that there was no specific SG system used in Saudi IBs. However, the system can generally be divided into two types. First, restricted SG system which focuses on the roles and attributes of SB members but ignores Shariah audit, applicable in most of IWs. Second, FFIBs applied comprehensive system which focuses with the roles of SB members and Shariah audit. In addition, the findings explored some factors affecting the system of SG such as, the major shareholders, the market, reputation of the banks and SAMA. The results revealed that the role of SB members can be identified as advisory, supervisory, executive or the combination of all the three together. However, the role of SB was advisory and supervisory in all FFIBs except one FFIB the role combined all the three. The study found that there were four important factors related to SB attributes namely: appointment, independence, transparency and confidentiality and competence of SB. In addition, the results found that there were two important factors related to operational procedures of SB i.e. meeting and decision and the issues related to new products. The results indicated that the main attributes related to Shariah audit were responsibilities, effectiveness and independence of Shariah auditors in Saudi IB. However, the significant functions were the scope and the procedures of Shariah audit. The research also found that there are two types of sources for Sariah non-compliant income (SNCI) generated in Saudi FFIBs and IWs. Some of IWs purify and distribute unlawful income while others do not. Instead, they refer such incomes to the conventional wing of the same bank. This study contributed to the existing body of knowledge on Shariah governance in general and Shariah governance in Saudi Arabia in particular. In addition, the study introduced significant role of internal audit in assuring Shariah compliance regardless of the role play by SB members and Shariah departments. Saudi regulators are expected to find this study informative in terms of the current practices of Shariah governance, issues and challenges faced by the Saudi IBs. Likewise, Saudi IBs may use the findings of this study in realizing the best practices within the sector of Saudi IBs.